From Shared Nature to Appropriete Nature – An Environmental History in the Serra de Petrópolis RJ - Winter, Valério (Geografares, 2017)
This work is part of a PhD research carried out at the UERJ Environmental History Research Laboratory. It is a Bibliographic Review that subsidized the analysis of texts and documents that is part of the research in progress. The objective is to understand how native populations, european and brazilian were related to nature in the conquest and occupation of the territory in which today is the city of Petrópolis RJ. We base our questions on authors from Cultural Geography and Environmental History. We ended by discussing the transformation of the place through the man/nature relation. A relation between the transformation of the local landscape and the modification of the inhabitants' perception of nature was observed.Keywords: Geography, Environmental History, Atlantic Forest.